Survey of the Kenyan Private Equity and Venture Capital Landscape - Divakaran, Shanthi (World Bank, Washington, DC, 2018)
This paper discusses the landscape for private equity and venture capital financing in Kenya. It provides an overview of the private equity and venture capital market in the country, describing key players, including funds, fund managers, investors, and public sector entities. The paper provides an analysis of key market drivers and impediments, as well as legal/regulatory/taxation drivers and impediments that affect Kenya’s private equity and venture capital industry.